\((2x-3)^3=13^3\)
\((2x-3)=13\)
\(2x=13+3\)
\(2x=16\)
\(x=16:2\)
\(x=8\)
\(@BaoTran\)
\((2x-3)^3=13^3\)
\((2x-3)=13\)
\(2x=13+3\)
\(2x=16\)
\(x=16:2\)
\(x=8\)
\(@BaoTran\)
Viết 13 ⋮ (2x + 3), ta nói
A. x là bội của 13 B. x là ước của 13
C. 2x + 3 là bội của 13 D. 2x + 3 là ước của 13
3^2x - (4^5-2x) = 13^10:3^2
3.(-2x+2/3)=13/3+x
7-(2x-1/3)^2=3
(2x+1/3)^2-3/8=1/8
12:[29-(x-2/3)^2]=3
(3x-1/2)^3+8/3=29/9-14/27
2(2x-1/3)^2+4/3=5/6+13/18
Tìm X
a) x-2=-6 2) -5x - (-3) =13 3)15-(x-7)=-21
b)2x-(-17)=15 5) |x-3| -7 =13
1) Tìm x:
a, x/-3=15/21
b, 13/-7=2x/5
c, 13/28=3/x-2
d, 3 - (2/3x)=(1/3) - 3
e, 3 - (1/3). x=(2/3)×-5
g, 5/8-(1_1/3)=2x-(1/2)
h, 3(x-1)=5/27
i, 2x-3= 7/3
Giúp mình nhanh nhanh nha! Mình đang rất vội!
tìm x
a)(x+1)+(x-3)=x-2
b)-(1-x)-(2x-3)=4-2x
c)-13-(5-x+6)+2x=3
3) (2x + 1) : 9 - 104:13 = 27 ^ 2 : 3 ^ 5
Tìm x
a) ( 2x -1)+3/15= 3/2
b) x+ 46/15= 1,5
c) ( -2x +1) + 3/15= 5/3
d) -13/3 -2x -1= 0,6
e) 3x -1/2x = 7/2-3
f) x÷5=6÷7
g) 2x-1/3 = 16/3
a) 3 - 2 ( x - 3 ) = 3x + ( - 5 )
b) - 6 - ( 7 + x ) = - 2 - 5 - 2x
c) 8x - 7 = - 13 + 7x
d) - 6 ( x - 2 ) + 5x = 13 - 2x
e) - 5 - 6x = x - 5x + 3